2020
DOI: 10.1055/s-0040-1716522
|View full text |Cite
|
Sign up to set email alerts
|

Are Plain X-Rays Necessary in the Diagnosis of De Quervain's Tenosynovitis?

Abstract: Background The routine use of plain radiography represents a significant expenditure and has been proven unnecessary in several orthopedic conditions. The utility of plain radiographs in the diagnosis of De Quervain's tenosynovitis (DeQ) is not clear. Questions/Purpose This study evaluates whether plain radiographic findings routinely predict the need for surgery or alter treatment courses in the initial diagnosis of DeQ. Patients and Methods A total of 200 patients who received wrist X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is possible that DeQ patients experience focal swelling at the radial side compared with the potential of generalized edema for CTS patients. [10][11][12] However, we found that the ratio of radiographic wrist edema is significantly larger in patients with DeQ compared with those with CMC and/or CTS. Furthermore, all radiographic measurements showed strong agreement for inter-and intraobserver reliabilities with the exception of the radialsided swelling, which only showed moderate agreement in the CMC group.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that DeQ patients experience focal swelling at the radial side compared with the potential of generalized edema for CTS patients. [10][11][12] However, we found that the ratio of radiographic wrist edema is significantly larger in patients with DeQ compared with those with CMC and/or CTS. Furthermore, all radiographic measurements showed strong agreement for inter-and intraobserver reliabilities with the exception of the radialsided swelling, which only showed moderate agreement in the CMC group.…”
Section: Discussionmentioning
confidence: 98%
“…(continued) ,10,38,40,43,49,57,58,66,76,89,101,104,107,111,127,128,[132][133][134]137,146,167,171,172,174,181,182,195,46,48,51,70,71,74,85,95,113,121,124,125,163,173,176,177,180,183,[187][188][189][190][191]201,202 Sex unclear or not reported5-7,9,10,34,38,40,45,50-52,54,55,63,65,67,68,71,73,76,80,81,83,84,88-90,96,98,99,101-103,106,109-111,113, …”
mentioning
confidence: 99%
“…46,48,51,70,71,74,85,95,113,121,124,125,163,173,176,177,180,183,[187][188][189][190][191]201,202 24 13.0 Case report36,47,53,56,60-64,78,91,94,118,120,122,130,139,145,148,160,165,179,184,193,194,200,206 114,116-118,125-137,139-141,167-175,186-188,194,195,200-206,208-211 7,40,47,49,51,61,62,67,71,90,122,128,133,145,150-155,158,159,161,162,187,191,195,199,201 …”
mentioning
confidence: 99%